2023
DOI: 10.1155/2023/6928117
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Severity of Metabolic Dysfunction-Associated Fatty Liver Disease and Serum Uric Acid to Serum Creatinine Ratio

Abstract: Purpose. As one of the most common chronic liver diseases, metabolic dysfunction-associated fatty liver disease (MAFLD) had different prognoses between mild and moderate-severe levels. Serum uric acid to serum creatinine ratio (sUA/Cr) can reflect the overall metabolic status of the body. To explore a convenient indicator to screen MAFLD and distinguish the severity of the disease, this study analyzed the correlation between sUA/Cr and the severity of MAFLD. Methods. 228 participants were enrolled and divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As the product of purine metabolism, uric acid is primarily metabolized by the kidneys, and its effect on ischaemic stroke may be modulated by renal function. Therefore, the recently proposed standardized uric acid level (SUA/SCr) as a new biomarker could more accurately reflect the net production of uric acid, aiding in the understanding of the complex interplay between metabolism and cardio-cerebrovascular diseases [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…As the product of purine metabolism, uric acid is primarily metabolized by the kidneys, and its effect on ischaemic stroke may be modulated by renal function. Therefore, the recently proposed standardized uric acid level (SUA/SCr) as a new biomarker could more accurately reflect the net production of uric acid, aiding in the understanding of the complex interplay between metabolism and cardio-cerebrovascular diseases [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we showed creatinine levels as an independent risk factor for FLD in children with Wilson’s disease. Previous studies have shown that the ratio of serum uric acid levels to creatinine levels is significantly associated with NAFLD and is positively correlated to the risk of moderate-to-severe FLD [ 36 ], which is an independent predictor of NAFLD [ 37 , 38 ]. A few studies have investigated the correlation between fibrinogen and laminin levels, a biochemical index to evaluate liver fibrosis, and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine, a chemical waste product of creatine, is affected by the number of muscles, food intake, and kidney function. The UCR represents the metabolic status, excluding the influence of kidney function [ 35 ]. The UCR has emerged as a new biomarker and is considered an excellent indicator of uric acid production [ 16 ].…”
Section: Discussionmentioning
confidence: 99%